Voters & voting an introduction - Evans, Jocelyn (London SAGE, 2004)
An accessible textbook that provides an overview of the historical origins and development of voting theory, this guide explores theories of voting and electoral behaviour at a level suitable for college students.
Keywords: Voting research; Voting research -- Methodology